IMPACT SAFE NUTRIENTS IN RAISING PRODUCTION AND CHMICAL CONTENTS OF POTATO - Al-Zaidi , M. A. H.; Al-Jumaili, M. A.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was amied to evaluating the efficiency of foliar fertilization with organic cobalt and environmentally friendly nutrients in improving production and chemical content of potatoes at the experimental fields of the College of Agricultural Engineering Sciences/ University of Baghdad.A factorial experiment (3×7) was applied using a Randomized Complete Block Design with three replications, the first factor was foliar fertilization with ATP SMART as an organic source of cobalt in three concentrations (0, 1, 2 ml L-1), the second factor includes foliar fertilization with aqueous solution of powdered cow's milk in two concentrations (10 and 20gL-1),and the bio stimulants STIMPLEX at two concentrations (5 and 10 ml L-1) and the aqueous solution of dry yeast at two concentrations (10 and 15 gL-1) as well as the control t.The results were revealed that spraying with ATP SMART (1 ml L-1) was able to record the highest values of the  leaves area (52.06 and 47.68 dcm2 plant-1) inboth seasons respectively, and treatment with (2 ml L-1) recorded the highest dry weight of the vegetative growth (41.34 and 39.05gplant-1) respectively for both seasons.The results showed the significant superiority of treatment (2 ml L-1) by recording the highest market production rate and tuber content of dry matter and starch in both season.The spraying with milk (20 g L-1)recorded the highest leaves area under the conditions of the spring season (57.13 dcm2 plant-1), and the treatment with yeast (10 g L-1) was superior in leaves area (51.49 dcm2 plant-1) in fall season.The foliar fertilization with (10gL-1yeastand 20gL-1milk) gave the highest number of marketable tubers production for both seasons.